EFEK KOMBINASI EKTRAK AIR DAUN JATI BELANDA, KEMUNING, MURBEI DAN RIMPANG BANGLE TERHADAP KADAR BUN DAN KREATININ SERUM PADA TIKUS WISTAR DENGAN DIET ATEROSKLEROSIS - Deanurva Calista Prima (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2018)
Introduction: Chronic hyperlipidemia leads to the excessive production of ROS (Reactive Oxygen Spesies) and the formation of atherosclerosis, in which both lead to kidney impairment. The administration of combined water extract of Jati Belanda, Kemuning, Murbei leaves and Bangle rhizome (JKMB) was traditionally used as anti-hyperlipidemia and antioxidant. This research aims to study the effect of JKMB water extract on serum BUN and creatinine levels of wistar rats with atherosclerosis diet.Methods : Laboratory experimental in vivo research method with post test control group only design. This research used 30 male wistar rats aged 2 months old which were divided into 5 groups: Negative Control (KN), Positive Control (KP), Group treated with Dose 1 (189mg/200gBB), Dose 2 (378mg/200gBB) and Dose 3 (756mg/200gBB). KP group and treatment groups are given with DTLM to induce atherosclerosis condition. DTLM was given along with the administration of JKMB for 12 weeks. A spectrophotometer with a wavelength of 600 nm and 510 nm is used for the examination of serum BUN and creatinine levels. Data analysis using SPSS version 16.Results: Induction of DTLM in KP did not increase the serum BUN and creatinine levels compared to KN. The combination of JKMB water extract increased serum BUN levels significantly (p <0.05) in D1 and D2 compared to KP, and D1 compared to D3. Whereas on creatinine level examination, the administration of JKMB water extract did not give any improvement (p> 0.05).Conclusion: Induction of DTLM did not increase serum BUN and creatinine levels in the KP group. The given JKMB water extract did not reduce serum BUN and creatinine levels in DTLM-induced wistar rats.